CHARNOCKITES FROM EAST ANTARCTICA AND THEIR GEOLOGICAL TYPIFICATION - Mikhalsky E.V.; Sheraton J.W.; Vladykin N.V. (My University, 2006)
Charnockitic rocks (orthopyroxene-bearing granitoids) are important and characteristic rocks exposed in East Antarctica. The origin of these rocks and their tectonic setting has been a matter of hot debate since the pioneering studies in Antarctica. The emplacement of intrusive charnockites was interpreted as an indication of cratonization of the Early Precambrian Antarctic Shield or its subsequent tectonic activity. The charnockitic rocks were regarded as intracontinental and anorogenic formations.
Keywords: charnockite; Antarctica